Tuning Ion Transport at the Anode‐Electrolyte Interface via a Sulfonate‐Rich Ion‐Exchange Layer for Durable Zinc‐Iodine Batteries (Adv. Energy Mater. 13/2023). Issue 13 (6th April 2023) - Zhang, Leiqian; Huang, Jiajia; Guo, Hele; Ge, Lingfeng; Tian, Zhihong; Zhang, Mingjie; Wang, Jingtao; He, Guanjie; Liu, Tianxi; Hofkens, Johan; Brett, Dan J.L.; Lai, Feili
Abstract : Zinc‐Iodine Batteries Polyiodide shuttling and dendritic growth are the major constraints for developing zinc‐iodine cells. In article number 2203790, Jiajia Huang, Feili Lai, and co‐workers revelation the corrosion mechanism of polyiodide on zinc, and develop a sulfonate‐rich ion‐exchange fiber layer to prevent polyiodide permeation. This layer also facilitates desolvation of Zn(H2 O)6 2+ and restricts the undesirable 2D diffusion of Zn 2+, thereby resulting in an advanced zinc‐iodine battery.